ARCHITECTURAL DECORATIONS OF ÇANKIRI CENTRAL DISTRICT TRADITIONAL HOUSES - Uğur DEMİRBAĞ (Fırat University, 2019)
The houses constitute the major parts of Çankırı’s historic urban fabric. Aside from some regional differences; the houses spreaded thick around the southren and westren hillsides of Çankırı Castle bear the traditional Turkish Houses features. With a general classification; Çankırı embodies the adobe filled timber framing, console supported plain outer sofa house types observed within the zone of Southren Anatolia civil architecture samples. In the former residential area of the city, the houses’ main façade overlooks South, fittingly with the structureof the land. Whereas the northren facades are closed. The fact that the main façades taking full advantage of the sun and the view of the hillside has allowed for the construction of inner sofa type house. The oldest examples of the houses are the inner sofa house types. Generally, the buildings have been constructed with gypsum braided, adobe filled timber framing. Whereas wooden materials are used in constructions without being processed in doors, windows, ceilings, floors, carpets, bathrooms, moldings and roof eaves. In some cases, various ornaments have been used in the ceilings of the structures, on the steps of the stair railing, on the doors, on the borders, in the sherbet and cabinets. Geometric and herbal beads are often used in houses. Generally, motifs are used geometrically as square, rectangular, diamond shaped slices, while leaf and daisy motifs are used as vegetative shapes. These ornaments stand out on the interior ceiling, on the doors and on the shelves. Apart from this, there are also ornaments made in the technique of çıtakâri and kündekâri. It is less common on the facades of residential houses. The ornamentation is seen on facades, especially on the surface of doors and pediments. In addition to this, the wooden consoles bearing the upper floors come up against each other.